2014
DOI: 10.1016/j.alcohol.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent ethanol access schedule in rats as a preclinical model of alcohol abuse

Abstract: One of the major challenges in preclinical studies of alcohol abuse and dependence remains the development of paradigms that will elicit high ethanol intake and mimic the progressive transition from low or moderate social drinking to excessive alcohol consumption. Exposure of outbred rats to repeated cycles of free-choice ethanol intake and withdrawal with the use of intermittent access to 20% ethanol in a 2-bottle choice procedure (IA2BC) has been shown to induce a gradual escalation of voluntary ethanol inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
306
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(333 citation statements)
references
References 82 publications
(229 reference statements)
21
306
5
1
Order By: Relevance
“…The alcohol-drinking animals were introduced to alcohol using an intermittent two-bottle free-choice paradigm, modified from Wise [20] and Wayner [21], and summarized by Carnicella et al [22]. On Tuesdays, Wednesdays, and Thursdays every week, the rats were given 24 h access to one bottle of water and one bottle of 20% alcohol (v/v).…”
Section: Voluntary Alcohol Intake and Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…The alcohol-drinking animals were introduced to alcohol using an intermittent two-bottle free-choice paradigm, modified from Wise [20] and Wayner [21], and summarized by Carnicella et al [22]. On Tuesdays, Wednesdays, and Thursdays every week, the rats were given 24 h access to one bottle of water and one bottle of 20% alcohol (v/v).…”
Section: Voluntary Alcohol Intake and Preferencementioning
confidence: 99%
“…We here introduce a free-choice intermittent access paradigm modified from the models used by Wise [20] and Wayner [21], summarized by Carnicella et al [22]. The animals had free access to 20% alcohol and water during three consecutive days followed by a four-day intermission with access to water only.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used strains of laboratory rats do not readily drink high quantities of alcohol unless sweet taste (eg, sucrose) fading techniques are used to induce it (see, eg, Samson, 1986;Czachowski and Samson, 2002), or animals are exposed intermittently to alcohol for a prolonged period of time under two-or three-bottle choice procedures (Wise, 1973;Simms et al, 2008;Carnicella et al, 2014), or are first made dependent by exposing them for long periods to alcohol in vapor chambers to induce drinking in withdrawal (Koob, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, this method does not address the motivational and reinforcing processes that regulate alcohol-intake and seeking, which are also critical in the development of addiction. Thus we used the operant selfadministration procedure to evaluate potential shifts in motivational behavior induced by the IA procedure to better model what occurs during the development of AUD in humans (285,318). We found that previous experience with operant alcohol selfadministration before IA two-bottle free choice preference drinking resulted in a faster acquisition of alcohol self-administration after the IA procedure and significantly increased lever-pressing for alcohol during self-administration compared to the non-IA controls (Figure 8 A-D).…”
Section: Intermittent Access To Alcohol Resulted In Escalated Alcoholmentioning
confidence: 99%
“…Bottles can be available either under continuously or under an IA schedule. IA drinking has been shown to escalate consumption faster and higher compared to continuous access drinking (285,286). Concentrations of alcohol between 10-20% (v/v) have been used.…”
Section: Alcohol-related Behaviorsmentioning
confidence: 99%